PENGARUH FEE AUDIT, AUDIT TENURE, ROTASI AUDIT DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT: Studi Empiris Pada Perusahaan Manufaktur Sektor Aneka Industri Dan Perusahaan Sektor Properti, Perumahan & Konstruksi Bangunan Yang Terdaftar Di Bursa Efek Indonesia - Luvena Luvena; Maidani Maidani; Raden Irna Afriani (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This research is based on both recent and current phenomena regarding audit quality, one of the phenomena that has become of interest in conducting this research such as the previous cases, namely the Enron case and the latest one as experienced by PT Garuda Indonesia. affect audit quality. . The purpose of this study is to examine the effect of audit fees, audit tenure, audit rotation and company size on audit quality and to develop a theory of planned behavior that contributes to the independent variables. The population in this study are all Manufacturing Companies in the Multi-Industrial Sector and Companies in the Property, Housing & Construction Sector listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used is purposive sampling method and obtained as many as 129 data samples. The analytical method used is Logistic Regression (Logistics Regression). The results showed that audit fees had a positive and significant effect on audit quality, while audit tenure, audit rotation and firm size had a positive but not significant effect on audit quality